The Effect of Aplikasi Edukasi Patuh Pakai Insulin (Aksi Patas) on Insulin Use Compliance and Glycemic Control in Diabetes Mellitus Patients at Prof. Dr. Margono Soekarjo Regional General Hospital - Sehat Dwi Prasaja; Devita Elsanti (Proceedings Series on Health & Medical Sciences, 2026)
Background: Diabetes mellitus is a chronic disease that requires lifelong management. Patient compliance in using insulin and good glycemic control are important factors in the management of diabetes mellitus. Low patient compliance and knowledge about insulin use are frequent problems. Objective: This study aims to determine the effect of obedient insulin education application (AKSI PATAS) on compliance with insulin use and glycemic control in patients with type 2 diabetes mellitus. Methods: This study is a pre-experimental study with a pre-test and post-test without control group design. The study sample was 18 patients with type 2 diabetes mellitus at Prof. Dr. Margono Soekarjo Purwokerto Hospital who were selected by purposive sampling. Data collection was done by questionnaire and examination of glycemic levels. Data analysis used paired t-test and Wilcoxon test. Results: There was a significant increase in family support, compliance with insulin use, and glycemic control after being given the AKSI PATAS educational application intervention (p<0.05). Conclusion: AKSI PATAS educational application has an effect in improving family support, compliance with insulin use, and glycemic control in patients with type 2 diabetes mellitus.